The association between Solar Lentigines and Type-2 Diabetes - Bobak Moazzami; Niloofar Razavi; Mansour Babaei; Motahareh Haghparast; Mohammad Ali Bayani (Babol University of Medical Sciences, 2017)
Background: Limited information exists between the associations of diabetes mellitus (DM) and solar lentigo (SL); a benign, common skin lesion characterized by hyperpigmented macules. Methods: This study was conducted on 90 patients diagnosed with DM and their age and sex matched controls who were referred to the Departments of Endocrinology at Babol University of Medical Science in Northern of Iran from January 2013 to December 2015. All demographic data including age, gender, occupation, family history of DM, estimated average sun exposure and presence of skin lesions were collected and analyzed. Results: Presence of SL was significantly higher among patients with DM compared to controls (61.9% vs 33.6%, P<0.001). After adjusting for age, sex and sun exposure rate, results indicated that DM was independently associated with the presence of SL (p=0.002). Stratifying patients based on gender, indicated that DM was significantly associated with SL in females (p=0.03), but not in male patients (p=0.06). Conclusion: The findings of the present study indicate that DM is an independent risk factor for the occurrence of SL lesions. These findings could represent a novel association between DM as a chronic oxidation state and SL as an early sign of aging.